MENGENALI KESULITAN BELAJAR PADA ANAK USIA SEKOLAH - Nur `Azizah; Alfi Sukrina, Hidayani Syam (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
As a teacher, it is certainly not uncommon to encounter children who have learning difficulties. Learning difficulties are indicated by the presence of certain obstacles to achieving learning outcomes. These difficulties can be psychological, sociological or physiological, causing the learning achievement to be below what it should be. This research is a literature study that will discuss children's learning difficulties. The results found that learning difficulties can be influenced by internal and external factors of students, so that before dealing with children's problems, a diagnosis is needed so that it is right on target. Keywords: learning difficulties, diagnosis, students